2011
DOI: 10.1111/j.1533-8525.2011.01203.x
|View full text |Cite
|
Sign up to set email alerts
|

All in the Family: Red States, Blue States, and Postmodern Family Patterns, 2000 and 2004

Abstract: In this article, we propose a new way of understanding presidential election outcomes in red and blue states in 2000 and 2004, one that takes into account state-level variation in postmodern family patterns. Using data from the Statistical Abstract, Census, the American Community Survey, and National Vital Statistics Reports, we construct two measures of state patterns of postmodern family formation (a father-absent family scale, and a small/delayed family scale). We find that these patterns of postmodern fami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…One of the greatest changes in American rural politics has been the transformation of the "solid South"-a Democratic fortress for a century after the Civil War-into an equally strong source of Republican votes (McKee 2008;Black 2004;hayes and McKee 2008). Republican success in rural America is also evident in much of the Midwest (Frank 2004;Bartels 2006;Francia and Baumgartner 2005;McVeigh and Diaz 2009;Monson and Mertens 2011;Gimpel and Karnes 2006). however, the Republican Party's dominance in rural America has not been uniform.…”
Section: Kenneth M Johnson Is a Professor Of Sociology And Senior Dementioning
confidence: 99%
“…One of the greatest changes in American rural politics has been the transformation of the "solid South"-a Democratic fortress for a century after the Civil War-into an equally strong source of Republican votes (McKee 2008;Black 2004;hayes and McKee 2008). Republican success in rural America is also evident in much of the Midwest (Frank 2004;Bartels 2006;Francia and Baumgartner 2005;McVeigh and Diaz 2009;Monson and Mertens 2011;Gimpel and Karnes 2006). however, the Republican Party's dominance in rural America has not been uniform.…”
Section: Kenneth M Johnson Is a Professor Of Sociology And Senior Dementioning
confidence: 99%
“…For instance, research has revealed that, relative to social liberals, social conservatives exhibit lower short-term mating orientation (STMO—i.e. interest in casual sex [ 7 , 8 ]), lower numbers of lifetime sexual partners [ 9 , 10 ], higher rates of marriage [ 11 ], younger ages of childbirth [ 12 ], more traditional family structures [ 13 ], and larger family sizes [ 14 ]. Evolutionary psychologists have theorized that these differences in mating strategies may create conflicts of interest, causing individuals to support the policies and social norms that facilitate their mating strategy [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The news media have chronicled the increased partisanship in Washington (Hulse and Herszenhorn 2009;Krugman 2002) and scholars have investigated changing regional divides among Americans, particularly in terms of how such differences translate into voting patterns (Cahn and Carbone 2010;Lesthaeghe and Neidert 2006;Monson and Mertens 2011). Our research weighs into this national discussion about growing cultural divides in the United States and provides some evidence to challenge this claim.…”
Section: Practice Implicationsmentioning
confidence: 78%